2023
DOI: 10.1002/pen.26302
|View full text |Cite
|
Sign up to set email alerts
|

Thermal‐oxidative aging and tribological properties of carbon nanotube/nitrile butadiene rubber composites with varying acrylonitrile content: Molecular dynamics simulations

Abstract: Nitrile butadiene rubber (NBR), a common material used in the stator rubber of screw pumps, usually undergoes severe thermal‐oxidative aging and wear at various temperatures and pressures. In this study, 1,2‐dihydro‐2,2,4‐trimethylquinoline (antioxidant RD) and carbon nanotubes (CNTs) were introduced into NBR to improve its thermal‐oxidative aging performance and reduce its wear. The thermal‐oxidative aging and mechanical and tribological properties of NBR composites with acrylonitrile (ACN) contents of 28%, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Chen et al calculated the bulk, shear, and Young's modulus of carbon nanotube (CNT)/ nitrile butadiene rubber (NBR) composites by the constant-strain method (Figure 1). The results indicated that the increase in acrylonitrile content improved the mechanical properties of the composite at constant CNT content, which is attributed to the polar interactions between the -CN groups [42]. Similarly, the elastic modulus of polymer/polymer composites such as Eucommia ulmoides gum (EUG)/natural rubber (NR), polyamide 66 (PA66)/graphene (GE), and polyimide (PI)/lanthana can be calculated with the assistance of MD simulation [43][44][45].…”
Section: Mechanical Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Chen et al calculated the bulk, shear, and Young's modulus of carbon nanotube (CNT)/ nitrile butadiene rubber (NBR) composites by the constant-strain method (Figure 1). The results indicated that the increase in acrylonitrile content improved the mechanical properties of the composite at constant CNT content, which is attributed to the polar interactions between the -CN groups [42]. Similarly, the elastic modulus of polymer/polymer composites such as Eucommia ulmoides gum (EUG)/natural rubber (NR), polyamide 66 (PA66)/graphene (GE), and polyimide (PI)/lanthana can be calculated with the assistance of MD simulation [43][44][45].…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…properties of the composite at constant CNT content, which is attributed to the polar in teractions between the -CN groups [42]. Similarly, the elastic modulus of polymer/poly mer composites such as Eucommia ulmoides gum (EUG)/natural rubber (NR), polyamide 66 (PA66)/graphene (GE), and polyimide (PI)/lanthana can be calculated with the assis tance of MD simulation [43][44][45].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…20 With the development of theoretical calculations, molecular dynamics (MD) simulation provides a new way to study the prediction of material properties and modification mechanisms, which can explore the properties of materials at the molecular level, while saving time. [21][22][23] Jang et al 24 explored the elastic and plastic properties of epoxy resin through MD simulations, revealing the deformation-to-failure mechanism of epoxy resin. Taking inspiration from the successful utilization of MD simulations in exploring material properties, our goal is to use this methodology to explore and predict the impact of physically blending PI with GNS and grafting PI onto GO on the performance of epoxy resin.…”
Section: Introductionmentioning
confidence: 99%
“…It is a promising channel to prepare the high‐performance rubber composites by nanofiller, such as nano marble, 12 nano silica, graphene, hydrotalcite, carbon nanotubes, zirconium phosphate and so on 13–15 . These nanofillers with excellent properties can make outstanding contributions to certain aspects of rubber properties such as mechanical properties, 16,17 thermal stability 18,19 and aging resistance 20 . However, in general, the elasticity of rubber will be greatly reduced after adding with the reinforced nanofillers 21,22 .…”
Section: Introductionmentioning
confidence: 99%